The Effect of Profitability and Leverage on Stock Prices with Company Size as a Control Variable (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2019-2023) - Mangande, Nelsy; Yuli, Astuti (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the effect of profitability and leverage on stock prices, with firm size as a control variable. Profitability is measured using Return on Assets (ROA), leverage is measured by the Debt to Equity Ratio (DER), while firm size is measured using the natural logarithm of total assets. The stock price used in this study is the year-end closing price. This is a quantitative study utilizing secondary data obtained from the annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample was selected using purposive sampling, resulting in a total of 198 companies that met the criteria. Data analysis was conducted using multiple linear regression with the assistance of EViews software. The results show that profitability has a positive and significant effect on stock prices, while leverage does not have a significant effect. Firm size, as a control variable, also shows a positive effect on stock prices. These findings indicate that financial performance, particularly a company's ability to generate profit, plays an important role in determining its market value.